Re-inventing Portuguese ceramic tiles: Using shape grammars as generative method and the impact on design methodology - Benrós, D.; Eloy, S.; Duarte, J. P. (Sixth International Conference on Design Cognition and Computation (DCC’14), Proceedings, 2014)
The following paper describes the process and results achieved with the workshop entitled ‘Re-inventing Portuguese ceramic tiles’ reflecting on design methodology and design teaching. Workshop participants were invited to rethink ceramic tile patterns developing a different process which used shape grammars as a generative system. Each participant group developed a three stage task using shape grammars principles and methodology. At a first stage all were exposed to the shape grammar formulation and rule system. At a second stage they had to explore shape rules and create a novel shape grammar. Each design solutions generated were presented for discussion. On the last stage all groups were presented with pre-existing patterns, invited to infer a grammar by extracting shape rules observed through design patterns and then extrapolate these findings to a third dimension. The preliminary results of stages two and three are of particular relevance in shape grammar research: shape grammar formulae does not constitute an intuitive process to most creative designers which are often trained to design singular solutions for a specific problem, more than one operative shape grammar can be formulated to represent the same corpus of solutions and lastly the generative potential of grammars transcends the normal capacities of the original grammarist aiding in design exploration and enlarging the corpus of feasible solutions. This paper also reflects on the impact of shape grammars as a design methodology.